New psychoactive substances in roadway crash victims in California - Gerona, Roy; Tomer, Daniel; Nielsen, Donovan; Sage, Allyson C.; French, Deborah; Tolles, Juliana; Chenoweth, James Alan (Frontiers in Toxicology, 2025)
BackgroundMotor vehicle crashes (MVCs) are a major global health concern. While alcohol continues to be a significant contributor to MVCs, the role of illicit and prescription drugs has increased in the last 4 decades. Moreover, the proliferation of new psychoactive substances (NPS) in the United States since 2010 has reshaped recreational drug use. Despite this, its contribution to MVCs has not been systematically evaluated. In this study, we report the prevalence of NPS in roadway crash victims in California.MethodsSerum samples from 1000 roadway crash victims were collected and analyzed using liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-QTOF/MS) against a comprehensive database of 1314 drugs, including 1008 NPS, and quantitative analysis was performed using isotope dilution. Alcohol was quantified in an autoanalyzer using an enzymatic method employing alcohol dehydrogenase.ResultsEight NPS (detection frequency = 26) were confirmed and quantified in 17 cases. Like current nationwide NPS surveillance studies, bromazolam, para-fluorofentanyl, and mitragynine were most frequently detected. NPS were detected in polypharmacy use, with traditional recreational drugs such as fentanyl, methamphetamine, and delta-9 THC most frequently co-detected. The serum geometric means detected for bromazolam (5.41 ng/mL; range: 0.22–26.59), para-fluorofentanyl (0.45 ng/mL; range: 0.28–2.02) and mitragynine (7.02; range: 0.55–90.55) were lower than those reported for overdose and death cases.DiscussionThis study is the first to report quantitative levels of multiple NPS and multiple NPS classes in a large US roadway crash survey, with the high detection of CNS depressants and their co-occurrence with traditional recreational drugs highlighting the need for expanded NPS testing, roadside testing strategies, and guidelines for determining drug-induced impairment; the quantitative data may be valuable in establishing these guidelines.